Perbandingan Penguasaan Materi Menggunakan Metode Pembelajaran PAIKEM dan Metode Ekspositori - Ariska, Yulia; Napratilora, Martina (Mitra PGMI: Jurnal Kependidikan MI, 2021)
In a series of teaching systems (curriculum), the method ranks after the material. Delivering material means nothing without involving the method. It always follows the material in the way of adjusting to its shape and style so that the method undergoes a transformation when the material presented changes. However, the same material can be used in different ways. The population in this study were two teachers of Islamic Religious Education at the 004 Sungai Piring State Elementary School, Batang Tuaka District. The data in this study were collected using observation and documentation techniques and analyzed using a t-test. From the results of data analysis, it concluded that there was no significant comparison between the implementation of PAIKEM learning and expository learning in Islamic Religious Education subjects at the 004 Sungai Piring State Elementary School, Batang Tuaka District.